Shear-flow-driven ion cyclotron instability of multicomponent magnetic field-aligned plasma flow - Chibisov, D.V.; Mikhailenko, V.S.; Stepanov, K.N. (Вопросы атомной науки и техники, 2011)
The ion cyclotron instability of magnetic field aligned sheared plasma flow with two H+ and ion species is investigated. The oxygen ions are assumed to be the active species while hydrogen ions are a background one, so that the frequency of oscillation approximately equals O+O+ cyclotron frequency. The threshold and growth rate of instability versus the flow velocity shear and relative concentration of oxygen ions are analyzed. Досліджено іонна циклотронна нестійкість зсуненого потоку плазми вздовж магнітного поля з двома видами, H+ і , іонів. Іони кисню вважаються основним видом, тоді як іони водню є фоном, так що частота коливань приблизно дорівнює циклотронній частоті іонів O+O+. Аналізується залежність порога та інкремента нестійкості від градієнта швидкості потоку і відносної концентрації іонів кисню. Исследована ионная циклотронная неустойчивость сдвигового течения плазмы вдоль магнитного поля с двумя сортами, H+ и , ионов. Ионы кислорода считаются основным видом, тогда как ионы водорода являются фоном, так что частота колебаний приблизительно равна циклотронной частоте ионов O+O+. Анализируется зависимость порога и инкремента неустойчивости от градиента скорости течения и относительной концентрации ионов кислорода.